369PInstitutional-based prospective molecular profiling of advanced solid tumours in Hong Kong: A report of 253 cases. (24th November 2019) - Loong, H; Chow, C; Ho, K; Fung, J; Koh, J; Chan, T-C; Leung, L K S; Yeo, W; Ma, B B Y; Chan, S L; Hui, E P; Lee, K W C; et al.
Abstract: Background: Molecular profiling of tumour tissue to guide treatment of patients (pts) with advanced solid tumours has previously been reported. Most series were reported from large volume academic cancer centres in the West. There is a paucity of data reporting the experience and applicability of such an approach in Asia. We report our single-centre experience of conducting a prospective molecular profiling programme for pts in advanced solid tumours. Methods: Pts with advanced solid tumours aged >/= 18 years, good performance status and archival tumour tissue available were prospectively consented. The RNA extracted from the FFPE tissue sections were subjected to RNA-sequencing using Archer FusionPlex Solid Tumor Kit and Archer Analysis Software 5.1. The putative gene translocations or alternative splicing were further confirmed with RT-PCR or FISH. Results: 253 pts consented between Feb 2017 and Feb 2019. Demographics: M:F 138 : 115; Median age = 58 (range: 19-89). Diseases included sarcomas (n = 88, 35%), NSCLC (n = 61, 24%), glioma (n = 42, 17%), melanoma (n = 7, 3%) and others (n = 55, 21%). Median turn-around time from consent to availability of report: 24 days (range: 3-112 days). 89% of samples passed quality control assessments. 8% (n = 21) of samples could not be processed due to insufficient material (n = 18), decalcified specimen (n = 2) and poor RNA quality (n = 1). 20 pts (9% of tested samples) had actionable genomic alterations identified that resulted in off-label use of directed anti-cancer therapies, referral to clinical trials or compassionate access programmes. These include EGFRvIII mutations (n = 7) and MET alterations (n = 2) in gliomas; ROS1 (n = 4), ALK (n = 2), MET exon 14-skipping (n = 1) and RET (n = 1) rearrangements in NSCLC; ALK rearranged sarcoma (n = 1). Across all diseases, 3 pts with NTRK fusions were identified. Conclusions: We report the first institutional-based molecular profiling programme in Hong Kong. Such programmes are feasible in Asia. Pts can potentially benefit from identification of actionable alterations within a reasonable time frame and be channelled to appropriate therapies or clinical trials. Legal entity responsible for the study: The Chinese University of Hong Kong. Funding: F. Hoffmann-La Roche Ltd (formerly Ignyta Inc.). Disclosure: H. Loong: Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Roche; Advisory / Consultancy: Celgene; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Eli Lilly; Advisory / Consultancy, Travel / Accommodation / Expenses: Boehringer Ingelheim; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Merck Sereno; Advisory / Consultancy, Speaker Bureau / Expert testimony: AbbVie; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Eisai; Speaker Bureau / Expert testimony: Guardant Health; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Bayer; Research grant / Funding (institution), Travel / Accommodation / Expenses: Merck Sharp & Dohme; Travel / Accommodation / Expenses: Pfizer; Advisory / Consultancy: Takeda ; Research grant / Funding (institution): Mundipharma. B.B.Y. Ma: Speaker Bureau / Expert testimony: Roche. E.P. Hui: Speaker Bureau / Expert testimony: Merck Sharp & Dohme; Speaker Bureau / Expert testimony: Merck Sereno; Advisory / Consultancy: Merck Sharp & Dohme; Research grant / Funding (institution): Merck Sharp & Dohme; Research grant / Funding (institution): Pfizer. All other authors have declared no conflicts of interest.